FEATURES OF THE LAND STRUCTURE OF THE PEASANTS OF STARODUBYE (SOUTH-WESTERN BRYANSK REGION) ACCORDING TO THE PEASANT REFORM OF 1861 - Muzychenko O.A. (Вестник Брянского государственного университета)
Based on archival documents, the article examines the features of the land structure of Starodubye peasants during the post-reform period. This historical region belonged in the second half of the XIX century to the north-eastern counties of the former Chernihiv province of the Russian Empire. They consisted of Starodubsky, Novozybkovsky, Mglinsky and Surazhsky counties. Now Starodubye belongs to the south-western part of the Bryansk region of Russia. The purpose of the article is to determine whether the peasants of Starodubye won or lost as a result of the Reform of 1861. We analyzed a large number of charters that are contained in the cases of the purchase of land plots by temporarily liable peasants of Starodubya in the Russian State Historical Archive. As a result, it was found that allotment lands could not provide the peasants with a living wage and the payment of ransom payments. Farmers often got inconvenient plots for cultivation. The peasants had to move their estates and various buildings to allotment land, which significantly complicated their life during the post-reform period. Landlords usually did not prevent peasants from using public areas, but limited their access to wood for heating houses. The dominant form of land use was communal, but sometimes landlords allowed the division of public land into farm plots.